Students’ Attitude Toward E- Learning During Covid 19 Pandemic At Informatics Department Of Universitas Pgri Sumatera Barat - Autila, Rani; Syafar, Dian Noviani; Yulmiati, Yulmiati (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study examined how students felt about online learning during the COVID 19 Pandemic at the Informatics Department of the University of Sumatera Barat. Students' ways of thinking, experiencing, or understanding the learning process might be influenced by their attitude. Teachers must therefore be aware of pupils' attitudes. Using empirical data, the researcher used this study to analyze how pupils think, feel, and behave. At the Informatics Department of Universiatas PGRI Sumatera Barat, the goal was to determine how the students' attitudes about thinking, feeling, and acting during the Covid 19 Pandemic influenced their usage of online learning. Research was conducted using a quantitative approach using either a survey or a descriptive design. Cross-sectional research was the study's research design. All students at Informatics Department session 2020 A are examined in this study of the twenty-three students of Universitas PGRI Sumatera Barat. The information was gathered using a survey. According to the study's findings, students exhibit a favorable attitude toward online learning, with a mean score of 3,5 (N = 23, st.d = 0.9). They behave negatively toward online learning, with a mean average of 2,9 (N=23, st.d = 1,0). Therefore, it is advised that teachers help their students transform their negative attitudes into good ones.